8 - Private Provision and Its Changing Interface with Public Higher Education: The Case of Kenya - Otieno, Wycliffe (Journal of Higher Education in Africa, 2007)
Like the rest of the continent, Kenya has a relatively long history of public provi- sion of higher education. Policy reforms in the 1980s resulted in the legitimate recognition of the private sector. Emerging competition has forced both sectors to adopt specific coping strategies, and foster different types of provision such as: traditional setting up of private institutions; privatization of public sector institu- tions; franchising and other forms of partnerships; and internationalisation. Pri- vate universities are also venturing into alternative modes of delivery like evening programmes. On the legal front, intense regulation of the private sector is leading to evident seriousness, but at the same time is giving the public sector an undue advantage over the private, as it remains largely unchecked.